Clinical effectiveness of fluorescence, digital images and ICDAS for detecting occlusal caries - Cristina Dupim PRESOTO; Tamara Carolina TREVISAN; Maria Costa de ANDRADE; Andrea Abi-Rached DANTAS; Juliana Alvares Duarte Bonini CAMPOS; Osmir Batista de OLIVEIRA-JUNIOR (Universidade Estadual Paulista, 2017)
Abstract Introduction The detection of small caries lesions is still a challenge for dental professionals who in their clinical practice have a wide variety of methods to detect caries on occlusal surfaces. Objective To clinically assess the effectiveness of the Vista Proof fluorescence camera, the Vista Cam digital intraoral micro camera and the International Caries Detection and Assessment System (ICDAS) visual criterion for detecting caries lesions on occlusal surfaces of permanent teeth. Material and method One hundred and seven posterior teeth from adult patients were examined visually and by means of digital radiographs by an examiner who rated them according to the presence or absence of occlusal caries. The teeth were then assessed by the other examiner using ICDAS, fluorescence and magnified digital images. The effectiveness of the methods was measured based on sensitivity, specificity, positive and negative likelihood ratio. For each method, the Receiver Operating Characteristic (ROC) curve and the Area Under the ROC curve (AUROC) were estimated. Result There was exceptional discrimination capacity for the intraoral images (AUROC=.93) and the ICDAS (AUROC=.91), with no significant statistical difference between them (z=.35, p=.73). The fluorescence exhibited an acceptable discrimination capacity (AUROC=0.78), although it was lower than the others. The positive likelihood ratio for the fluorescence was only 2.32, compared to 20.58 for the intraoral image and 58.11 for the ICDAS. Conclusion Both methods and the ICDAS exhibited an adequate clinical performance, although the ICDAS and intraoral image were more effective than the fluorescence.